2023
DOI: 10.1002/smmd.20230016
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared light‐responsive Nitric oxide microcarrier for multimodal tumor therapy

Danna Liang,
Gaizhen Kuang,
Xiang Chen
et al.

Abstract: Nitric oxide (NO) has shown great potential in tumor therapy, and the development of a platform for precise and controllable NO release still needs to be explored. Herein, a microfluidic electrospray strategy is proposed for the fabrication of hydrogel microspheres encapsulating NO donors (S‐nitrosoglutathione, GSNO) together with black phosphorus (BP) and chemotherapeutic doxorubicin (DOX) as microcarriers for tumor therapy. Based on the excellent photothermal property of BP and thermal sensitivity of GSNO, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…16,17 For example, NO- and H 2 S-mediated PTT can exhibit an enhanced synergetic efficiency on bacterial inhibition (over temperatures ranging from 50 °C to 55 °C) and can promote immunomodulatory cell migration as well as angiogenesis for infected wound healing. 18–22 Despite numerous studies on H 2 S- and NO-mediated PTT, CO-mediated PTT is rarely reported for wound healing, 23 and neither its therapeutic effect nor mechanism has been explored for use in infected diabetic wound healing yet.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 For example, NO- and H 2 S-mediated PTT can exhibit an enhanced synergetic efficiency on bacterial inhibition (over temperatures ranging from 50 °C to 55 °C) and can promote immunomodulatory cell migration as well as angiogenesis for infected wound healing. 18–22 Despite numerous studies on H 2 S- and NO-mediated PTT, CO-mediated PTT is rarely reported for wound healing, 23 and neither its therapeutic effect nor mechanism has been explored for use in infected diabetic wound healing yet.…”
Section: Introductionmentioning
confidence: 99%